A three-dimensional numerical investigation of a novel shallow bore ground heat exchanger integrated with phase change material. (5th November 2019) - Zhang, Mingkan; Liu, Xiaobing; Biswas, Kaushik; Warner, Joseph
Highlights: Introduced a shallow bore ground heat exchanger (GHE) with phase change materials. New GHE is ten times shorter than a conventional vertical bore GHE. Validated three-dimensional numerical models for both the new and conventional GHEs. New GHE has better performance than conventional GHE under daily high thermal loads. Abstract: The heat transfer performance of an innovative design of ground heat exchanger, called underground thermal battery (UTB), was investigated in this paper. The UTB is designed to be installed in a shallow subsurface of the ground (less than 20 ft or 6 m below the grade), which is much shallower than the vertical bores (deeper than 200 ft or 60 m) required for installing conventional vertical bore ground heat exchangers (VBGHE). The UTB consists of a water-filled tank that also contains a phase change material (PCM), which impart the UTB a large thermal storage capacity. A three-dimensional (3D) numerical model has been developed to evaluate the performance of the UTB and to compare it with a conventional VBGHE. The simulation results indicated that a UTB can better regulate the entering water temperature of a ground source heat pump (GSHP) for more efficient operation than a conventional VBGHE under short-term high thermal load conditions. In addition, the UTB can make more effective use of PCMs compared with using PCMs to replace the conventional grouting material in a VBGHE.